Linear differential equations for families of polynomials - Taekyun Kim; Dae San Kim; Toufik Mansour; Jong-Jin Seo (Journal of Inequalities and Applications, 2016)
Abstract In this paper, we present linear differential equations for the generating functions of the Poisson-Charlier, actuarial, and Meixner polynomials. Also, we give an application for each case.